Virtual reality in sport and wellness: Promise and reality - Katz, L.; Parker, J.; Tyreman, H.; Kopp, G.; Levy, R.; Chang, E. (International Journal of Computer Science in Sport, 2006)
Virtual reality ha s been used to help land a person on the moon and to instruct astronauts on how to manipulate the space arm. The military uses virtual environments to prepare soldiers for combat and airlines use virtual reality simulators to train and qualify pilots. Increasingly, game manufacturers are utilizing virtual environments and haptic devices to capture the attention of their adherents. However, many questions remain to be answered. How does one define virtual reality and virtual environments? How can virtual reality environments and simulations be used effectively in sport and wellness situations? Will coaches, athletes, and wellness specialists utilize the tools? What has been accomplished so far and what promises have been made? Do the benefits justify the costs? The reality maybe short of the promise, but can the gap be closed - virtually? This paper explores the promise of virtual reality, the nature of virtual reality environments, examples of existing applications, and a discussion of the research to date. It also provides a vision for the future.